1980
DOI: 10.2337/diab.29.6.475
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal Degradation of Receptor-bound 125I-labeled Insulin by Rat Adipocytes: Its Characterization and Dissociation from the Short-term Biologic Effects of Insulin

Abstract: In this study we used chloroquine to characterize the interalization and lysosomal degradation of receptor-bound 125I-insulin by rat adipocytes and to determine the role of lysosomal processing of insulin in the short-term biologic effects of the hormone. Chloroquine inhibited the degradation of 125I-insulin bound to adipocytes by both association and disslociation experiments. In the former experiments, chloroquine caused a time- and concentration-dependent increase in specifically bound insulin owing to an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
2

Year Published

1982
1982
2003
2003

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(19 citation statements)
references
References 47 publications
2
15
2
Order By: Relevance
“…The functional relationship between the degradation and short-term biological effects of insulin in adipocytes had been examined in the presence of the lysosomotropic agent chloroquine. These experiments indicated that insulin degradation was not a prerequisite for biological action (Suzuki & Kono, 1979;Hammons & Jarett, 1980;Marshall & Olefsky, 1980). Cultured foetal hepatocytes have been shown to bind insulin specifically and to respond to the presence of the hormone by an enhanced ability to synthesize glycogen (Plas et aL, 1979; Menuelle & Plas, 1981).…”
mentioning
confidence: 99%
“…The functional relationship between the degradation and short-term biological effects of insulin in adipocytes had been examined in the presence of the lysosomotropic agent chloroquine. These experiments indicated that insulin degradation was not a prerequisite for biological action (Suzuki & Kono, 1979;Hammons & Jarett, 1980;Marshall & Olefsky, 1980). Cultured foetal hepatocytes have been shown to bind insulin specifically and to respond to the presence of the hormone by an enhanced ability to synthesize glycogen (Plas et aL, 1979; Menuelle & Plas, 1981).…”
mentioning
confidence: 99%
“…4 ' 15 ' 17 - 18 The ability of chloroquine to lower the level of low-mol-wt degradation products released into the medium may indicate that at least part of the degradation is in the lysosomes. 24 Pre-exposure of the endothelial cells to insulin led to downregulation of its cell surface receptor sites, as described for other cell systems. 1i17 ' 21 It should be emphasized that all our studies were performed with cells attached to culture dishes, in which only the apical cell surface is fully available for hormone binding.…”
Section: Discussionmentioning
confidence: 86%
“…Failure of ammonium chloride, leupeptin, and colchicine to block or enhance insulin-like responses is not surprising in view of the rapidity in onset of some insulin-like responses (15)(16)(17)(18)(19)(20)(21)(22) and the failure of some of these agents to interfere with similar actions of insulin in adipocytes (23). Even under conditions in which hormone degradation was severely impeded by agents that act at various loci, we could detect no impairment or enhancement of the three biological responses tested.…”
Section: Discussionmentioning
confidence: 99%